2015
DOI: 10.1007/s11999-015-4205-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Arm Muscle Fatigability With Cognitive Demand in Older Adults

Abstract: Background Muscle fatigability can increase when a stressful, cognitively demanding task is imposed during a low-force fatiguing contraction with the arm muscles, especially in women. Whether this occurs among older adults ([ 60 years) is currently unknown. Questions/purposes We aimed to determine if higher cognitive demands, stratified by sex, increased fatigability in older adults ([ 60 years). Secondarily, we assessed if varying cognitive demand resulted in decreased steadiness and was explained by anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…The magnitude of endurance time impairment reported in the current study was −13% and −25% in 1‐back and 2‐back, respectively, compared to control condition. These findings are consistent with previous studies reporting a similar range of decline in endurance time during CMDT (i.e., ~−10 to −25%) using concomitant complex mental‐math tasks (Keller‐Ross et al, ; Pereira et al, ; Yoon et al, ). However, in these three studies, endurance performance was unchanged compared to a simple mental‐math task condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The magnitude of endurance time impairment reported in the current study was −13% and −25% in 1‐back and 2‐back, respectively, compared to control condition. These findings are consistent with previous studies reporting a similar range of decline in endurance time during CMDT (i.e., ~−10 to −25%) using concomitant complex mental‐math tasks (Keller‐Ross et al, ; Pereira et al, ; Yoon et al, ). However, in these three studies, endurance performance was unchanged compared to a simple mental‐math task condition.…”
Section: Discussionsupporting
confidence: 92%
“…One of our hypotheses was that the development of neuromuscular fatigue could have been modified during CMDT compared to a control condition, explaining in part the decrease in endurance performance. In accordance with previous studies (Keller-Ross et al, 2014;Pereira et al, 2015;Yoon et al, 2009), we found a similar amount of neuromuscular fatigue at TF (i.e., identical decrease in MVC between conditions), despite significantly lower endurance time in both CMDT compared to control. With the aim to clarify the origin of the neuromuscular impairments, we investigated the kinetics of peripheral and central mechanisms of fatigue throughout two CMDT protocols and a control condition.…”
Section: Mechanisms Underlying Reduced Performance During Cmdtsupporting
confidence: 93%
“…Both old and young women had greater increases in fatigability than men when the cognitive challenge (counting backwards by a two digit number) was imposed during an isometric fatiguing contraction sustained at 20% maximal voluntary isometric contraction with the elbow flexor muscles (52, 69). Certainly, there are widespread sex differences in brain activation (10) during cognitive tasks with some, but minimal, differences during motor tasks (99).…”
Section: Current Knowledge On Sex Differences In Performance Fatigmentioning
confidence: 99%
“…Each participant was seated upright in an adjustable chair, with the nondominant arm abducted slightly to the participant's side and the elbow resting on a padded support with the elbow joint flexed to 90°. The setup was similar to that described previously (57,58). In brief, the forearm was placed in a modified wrist/hand/thumb orthosis (Orthomerica, Newport Beach, CA), and the forearm was placed midway between pronation and supination.…”
Section: Forcementioning
confidence: 99%